Good Government Governance In The Internal Control System And Audit Opinion - Agus Bandiyono (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
This study wants to describe the impact of the implementation of the internal control system in the Governance of local governance to the audit opinion CPCs local governments achieved with the application of the principles of good government governance as a moderator variable. This study is a descriptive quantitative study that seeks to describe an application of an internal control system to BPK's audit opinion by applying the principles of good government governance as a moderating variable. Respondents in this study were OPD-OPDs in the Banten Province government, Pandeglang Regency Government, and Serang City Government. The data used in the analysis of this research is data that comes from a questionnaire which is then filled in by the respondent. SEM PLS is used as a tool to analyze the data in this study. The results of this study indicate that the implementation of a good internal control system can have a positive and significant impact on the audit opinion of BPK RI. The moderator variable in the application of the principles of good governance is also able to act as a moderating variable, namely being able to increase a positive and significant impact on the Audit Opinion Raihan BPK.